ANALISIS PEMENUHAN KEBUTUHAN INFORMASI KEAGAMAAN PADA KOMUNITAS ONE DAY ONE JUZ (ODOJ) - Srimulyo, Koko; Alifiana, Amalia Ayu (Program Studi Ilmu Perpustakaan, Fakultas Adab dan Ilmu Budaya, UIN Sunan Kalijaga Yogyaka, 2023)
This study aims to determine cognitive conditions before and after fulfilling religious information needs as a concern (gap) in the One Day One Juz (ODOJ) community, as well as to find out the ways ODOJers achieve to reduce or eliminate cognitive anxiety (cognitive gap) information. Subjects and methods: The sample stratification is 100 ODOJers in the Surabaya area with qualifications to participate in NGAOS/KOMINEX activities at least 4 times a month, take part in ODOJ online studies at least 4 times, and they are 15 years old. The conclusion is, there is confusion among ODOJers before the fulfillment of information occurs due to the large and varied data. This was immediately resolved after the fulfillment of the information needed (applicable) and disseminated to others. There is satisfaction that is achieved after the fulfillment of religious information needs.